The impact of canonical Wnt transcriptional repressors TLE3 and TLE4 on postsynaptic transcription at the neuromuscular junction - Gessler, Lea; Huraskin, Danyil; Eiber, Nane; Hashemolhosseini, Said (Frontiers in Molecular Neuroscience, 2024)
Here, we investigated the role of the canonical Wnt signaling pathway transcriptional regulators at the neuromuscular junction. Upon applying a denervation paradigm, the transcription levels of Ctnnb1, Tcf7l1, Tle1, Tle2, Tle3, and Tle4 were significantly downregulated. A significant decrease in canonical Wnt signaling activity was observed using the denervation paradigm in Axin2-lacZ reporter mice. Alterations in the transcriptional profile of the myogenic lineage in response to agrin (AGRN) suggested that TLE3 and TLE4, family members of groucho transducin-like enhancer of split 3 (TLE3), transcriptional repressors known to antagonize T cell factor/lymphoid enhancer factor (TCF)-mediated target gene activation, could be important regulators of canonical Wnt signaling activity at the postsynapse. Knockouts of these genes using CRISPR/Cas9 gene editing in primary skeletal muscle stem cells, called satellite cells, led to decreased AGRN-dependent acetylcholine receptor (CHRN) clustering and reduced synaptic gene transcription upon differentiation of these cells. Overall, our findings demonstrate that TLE3 and TLE4 participate in diminishing canonical Wnt signaling activity, supporting transcription of synaptic genes and CHRN clustering at the neuromuscular junction.